THE TRANSLATION OF ENGLISH PLURAL NOUN INTO INDONESIAN - Noverino, Romel (Prosiding PESAT, 2013)
English and Indonesian have different set of rules in terms of grammar and one of the differences, which is the focus of this research paper, is formations of plural noun in English and Indonesian and its relation to how to translate English plural nouns into Indonesian from points of view of morphology, syntax, and semantics. English has formal feature to indicate plural noun while Indonesian does not. This paper is meant to provide explanations of English plural noun and Indonesian plural noun formations and to explain the ways on how to translate English plural nouns into Indonesian. Data were taken from two novels: English version One, Two, Buckle My Shoe by Agatha Christie and Indonesian version Satu, Dua, Pasang Gesper Sepatunya (Language switching) by Alex Tri Kentjono W. Results showed thatthere are two major ways in translating English plural noun into Indonesian, namely1)Translation of English plural noun into Indonesian in the form of reduplication; 2)Translation of English plural noun into Indonesian notin the form of reduplication.